THE IMPORTANCE OF SHARIA ACCOUNTING IN FINANCIAL BUSINESS (SHARIA) INSTITUTIONS - Syafrida Putri (RADJA PUBLIKA, 2023)
Islam is a religion guided by the Koran. Our life needs enlightenment, don't make the mistake of entering and doing bad deeds that can harm and affect others. Islam is also called a complete package because Islam teaches not only one thing but teaches many important things that are useful in everyday life for the future. Islam as a religion is placed as an alternative as well as its teachings are taught to be used as a guide in the lives of people who adhere to it. Thus, its existence provides direction for the development of human civilization, especially in the field of science and technology.